2020
DOI: 10.1111/1756-185x.13826
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Andersson lesion treatment in ankylosing spondylitis: A medical record review study focused on medium‐ to long‐term outcomes

Abstract: The present study aimed to evaluate the clinical efficacy of Andersson lesion (AL) treatments and prognostic factors using medium-to long-term follow-up data and discuss the clinical characteristics and treatment of AL. Forty-eight consecutive AL cases at our center from June 2011 to March 2018 were retrospectively analyzed, including 13 cases treated conservatively and 35 treated surgically. Epidemiological characteristics, treatment modalities, clinical features and outcomes, and prognostic factors of the Ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…The possible reasons for misdiagnosis of ALs include unawareness of these lesions and their radiographic resemblance to other destructive lesions of the spine, such as infective spondylodiscitis, spinal tuberculosis, and tumors. [ 10 ] Merely using PR to detect ALs may account for the missed diagnosis of these lesions. A study by Kim et al [ 12 ] revealed that PR might underestimate the prevalence of ALs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The possible reasons for misdiagnosis of ALs include unawareness of these lesions and their radiographic resemblance to other destructive lesions of the spine, such as infective spondylodiscitis, spinal tuberculosis, and tumors. [ 10 ] Merely using PR to detect ALs may account for the missed diagnosis of these lesions. A study by Kim et al [ 12 ] revealed that PR might underestimate the prevalence of ALs.…”
Section: Discussionmentioning
confidence: 99%
“…[ 9 ] The delayed diagnosis and management of ALs may contribute to the patients’ progressively deteriorating pain or kyphotic deformity, and may even cause neurologic deficits resulting from the overgrowth of fibrous or osseous tissue and subsequent spinal stenosis. [ 9 , 10 ]…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonetheless, persistent movement of AL segments will still impede the bony healing and union of erosive discovertebral fractures despite the employment of pharmacological and immobilized strategies, resulting in potential spinal cord injury. Therefore, surgical approaches are commonly used to reestablish spinal stability for late-stage ALs to alleviate ongoing back pain, correct kyphotic deformity, and recover neurologic status efficiently ( 26 ); such approaches include spinal canal decompression, transpedicular fixation, and vertebral fusion, which show optimal clinical alleviation with desirable efficacy in medium- to long-term follow-up ( 27 ). Likewise, it was suggested that internal spinal stabilization is a decent surgical approach for fractured lesions in DISH ( 28 , 29 ).…”
Section: Discussionmentioning
confidence: 99%